DAMPAK KEBEBASAN EKONOMI TERHADAP PERTUMBUHAN EKONOMI - Agustina Suparyati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
The purpose of this study is to examine the effect of economic development on economic growth. Economic freedom as an indicator of the progress of a country's welfare level consisting of 10 constituent components namely Property Rights, Freedom from Corruption, Fiscal Freedom, Government Spending, Business Freedom or Regulatory Freedom, Labor Freedom, Monetary Freedom, Freedom Trade, Investment Freedom and Financial Freedom. This study uses annual quantitative data in the span of time between 2001-2012 with the object of research in developed countries in Asia (Japan, China, South Korea and Singapore) and developing countries in Asia (Indonesia, Malaysia, Laos, Thailand, Philippines, Singapore and Vietnam ) The results obtained that in ASEAN countries the variables that affect economic growth are variables of right property, business freedom, trade freedom and financial freedom while in developed countries in Asia, the components of influential economic freedom are property right, freedom from corruption, government spending, monetary freedom , business freedom, and financial freedom.